Study of density control algorithm based on optimization of vacant energy consumption in heterogeneous sensor networks - LIU Lin-feng; ZOU Zhi-qiang; ZHANG Deng-yin; WANG Ru-chuan (Tongxin xuebao)
The scheme of gradually topology expansion was adopted,and a density control algorithm DCA aiming to reduce the vacant energy consumption was presented for heterogeneous WSN. A connected coverage set based on minimizing vacant energy consumption can be found by DCA,and the set would be mapped into the active nodes set finally. Both theoretical analysis and experimental data suggest that DCA can achieve well-constructed topology and prolong network lifetime effectively.